2015
DOI: 10.1136/ejhpharm-2015-000735
|View full text |Cite
|
Sign up to set email alerts
|

Assistance of family carers for patients with COPD using nebulisers at home: a qualitative study

Abstract: ObjectiveFor many patients with chronic conditions, such as chronic obstructive pulmonary disease (COPD), the assistance of family carers with medicines is vital for optimal treatment outcomes. The aim of this study was to identify the assistance carers provide to patients with COPD using nebuliser-delivered therapy at home, and the problems experienced that may impact on the safety and effectiveness of therapy and contribute to carer burden.MethodsA cross-sectional, qualitative descriptive study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
6
0
4
Order By: Relevance
“…Concerns or issues about managing medication, as evidenced by the extensive literature available on this topic (Alhaddad, Taylor, Robertson, Watman, & Smith, ; Look & Stone, ; Maidment et al, ; Wingham et al, ), was noticeably absent from our data. This was surprising given that pharmacists are well placed to address medication‐related issues.…”
Section: Discussionmentioning
confidence: 64%
“…Concerns or issues about managing medication, as evidenced by the extensive literature available on this topic (Alhaddad, Taylor, Robertson, Watman, & Smith, ; Look & Stone, ; Maidment et al, ; Wingham et al, ), was noticeably absent from our data. This was surprising given that pharmacists are well placed to address medication‐related issues.…”
Section: Discussionmentioning
confidence: 64%
“…Also, one of the patients reported that he does need somebody to make sure he is doing it properly. 6 Overall, the review showed that there is lack in knowledge about the proper dilution of medication with many study participants.…”
Section: Knowledgementioning
confidence: 99%
“…The study reported that about 22 participants (n = 50) failed to ensure it prior to filling the drugs. 4 Another study conducted by Alhaddad and colleagues 6 reported that the patient caretaker found it difficult to set the nebulizer at home. This study was conducted among 14 participants in which 8 participants experienced difficulty in setting up and operating the nebulizer.…”
Section: Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Nebulisers prove difficult to use, as they require device assemblies, dosage, diluent often combined, inhaled for a few minutes and then disassembled, cleaned, sanitized and dried [4].…”
Section: Introductionmentioning
confidence: 99%